PERBEDAAN SENSITIVITAS PENGECAPAN RASA ASIN AKIBAT PEMAKAIAN OBAT KUMUR BERALKOHOL - Dwi Putri Arianti; Zulkarnain Agus; Susi Susi (Faculty of Dentistry Universitas Andalas, 2014)
Mouthwash is a product used to maintain oral hygiene. Most of mouthwash contains alcohol with concentration > 0 ≤ 27% which is used as solvent, preservative, flavour carrier and as an antibacterial. The effect of using mouthwash containing alcohol is that alcohol as drying agent, decreases in salivary flow, produced metabolites acetaldehyde and causes degeneration of nerve endings that can decrease the sensitivity of tasting. This study aimed to determine the differences of salty tasting due to using mouthwash containing 27% alcohol in 15 days. This research used a pretest and posttest group. The first group used mouthwash containing 27% alcohol and the second group used non-alcohol mouthwash. The first step, NaCl solution was dropped on the surface of the right lateral part of the anterior tongue from low to high concentration until the sample could taste the salty taste. Sample used mouthwash in 15 days according to the direction of usage on the bottles of mouthwash. The last step, NaCl solution was dropped on the surface of the right lateral part of the anterior tongue from low to high concentration until the sample could taste the salty taste. Data analysis using Wilcoxon Signed Ranks Test and Mann-Whitney test. The results showed significant differences between the two groups (p = 0.001). Salty taste sensitivity because of the usage 27% alcohol-containing mouthwash was lower than non-alcohol mouthwash. The conclusion is there will be decreasing of salty taste sensitivity because of the usage 27% alcohol-containing mouthwash in 15 days.